2020
DOI: 10.1111/grs.12298
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation and aerobic stability of Napier grass silage treated with different levels of citric acid residue

Abstract: The experiment was conducted to investigate the effects of different levels of citric acid residue (CAR) on the fermentation quality and aerobic stability of Napier grass. Napier grass was ensiled with no additives control (CON), 1.2% CAR (C1), 3.6% CAR (C2) and 6.0% CAR (C3) on a fresh weight basis in laboratory silos for 3, 6, 9, 15 and 45 days. After opening the silos, the silages were subjected to analyzing the chemical and microbial compositions, and the residual silages ensiled for 45 days were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
2
4
0
Order By: Relevance
“…These results agree with the results of Zhang et al (2016) and Sun et al (2020), who reported declining organic acid concentrations in L. chinensis silage from 30 to 45 days and from 30 to 90 days, respectively. Other previous studies also observed the decline in rehydrated corn kernel silage (Carvalho et al, 2016), smooth bromegrass silage (Niu et al, 2018), barley silage (Liu et al, 2019), whole-plant corn silages treated with inoculants (Gharechahi et al, 2017;Guan et al, 2020;Xu et al, 2020), and Napier grass silage (Tao et al, 2021). These results suggest that the declining concentration of volatile components (organic acids and ammonia-N) during late fermentation is a universal phenomenon in silage and needs further research.…”
Section: Volatile Products Of Leymus Chinensis Silagesupporting
confidence: 63%
“…These results agree with the results of Zhang et al (2016) and Sun et al (2020), who reported declining organic acid concentrations in L. chinensis silage from 30 to 45 days and from 30 to 90 days, respectively. Other previous studies also observed the decline in rehydrated corn kernel silage (Carvalho et al, 2016), smooth bromegrass silage (Niu et al, 2018), barley silage (Liu et al, 2019), whole-plant corn silages treated with inoculants (Gharechahi et al, 2017;Guan et al, 2020;Xu et al, 2020), and Napier grass silage (Tao et al, 2021). These results suggest that the declining concentration of volatile components (organic acids and ammonia-N) during late fermentation is a universal phenomenon in silage and needs further research.…”
Section: Volatile Products Of Leymus Chinensis Silagesupporting
confidence: 63%
“…Lactic acid bacteria additives induce different types of fermentation Lactobacillus plantarum undergoes homolactic fermentation, while Lactobacillus buchneri undergoes heterogeneous fermentation (Addah et al, 2014;Li et al, 2021). The product of homolactic fermentation is lactic acid, which rapidly reduces the pH value of the silage, thereby inhibiting the activities of other microorganisms (Tao et al, 2021;Xie et al, 2021). However, in addition to lactic acid, heterogeneous fermentation also produces substances such as ethanol, acetic acid, and carbon dioxide, among which acetic acid can effectively inhibit the reproduction of harmful microorganisms (Si et al, 2018;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of counts of microorganisms, 10 g of fresh silage was tenfold serially diluted by 0.85% sodium chloride [33]. The population of the lactic acid bacteria (LAB) and the yeast were cultured in the MRS Agar medium and potato glucose agar medium, respectively.…”
Section: Nutritional Composition and Microbial Populationmentioning
confidence: 99%